A Methodology of Knowledge Management Strategy based on the Knowledge Spiral Model: Case Study Two Iranian Organizations - Yosef Mohammadi Moghadam; Amir Behboodi; Roya Hamze; Ghazale Khoda'i (مطالعات مدیریت کسب و کار هوشمند, 2016)
To evaluate and select appropriate knowledge management strategy, a lot of organizational factors should be considered. Processes of knowledge creation, knowledge sharing, knowledge retention, and knowledge acquisition are involved in the selection of appropriate strategies. In this study, a methodology is offered to develop a knowledge management strategy. With regard to the infrastructure and processes of knowledge management bottlenecks of spiral knowledge processes are identified. Accordingly, strategic solutions are formulated for organizations. A review of the theoretical foundations of previous studies and factors affecting organizational knowledge management strategies have been explored from frameworks and administrative procedures. In this methodology, factors which influences on knowledge management strategy are as follows: organizational structure, corporate culture, information technology, human resource strategies and processes of knowledge sharing, knowledge capture, knowledge acquisition, and knowledge creation. In this study, the effect of mutual impact of organizational structure, IT and human resource management strategies on knowledge management strategy with the approach in knowledge spiral of the organization is emphasized. The proposed methodology was confirmed with a survey of 36 organizations and academic experts. At the end, the methodology was implemented to 2 different organizations and the results were analyzed.